The potential benefit of allogeneic over autologous transplantation in patients with very early relapsed and refractory follicular lymphoma with prior remission duration of ≤12 months. (5th February 2016) - Lunning, Matthew A.; Migliacci, Jocelyn C.; Hilden, Patrick; Devlin, Sean M.; Castro‐Malaspina, Hugo; Giralt, Sergio; Perales, Miguel‐Angel; Zelenetz, Andrew D.; Moskowitz, Craig H.; Sauter, Craig S.
Summary: Early relapsed or refractory follicular lymphoma (FL) warrants consolidation with transplantation, though graft source modality remains controversial. We analysed the outcomes of 44 patients transplanted with either autologous or allogeneic graft sources in the post‐rituximab era. No difference in event‐free (EFS) or overall survival (OS) was observed between allogeneic (81% and 81%) and autologous transplantation (64% and 70%) at 3 years. There was a significant difference in EFS between allogeneic and autologous transplantation patients with previous remission duration of ≤12 months (80% and 42% at 3 years, P < 0·015). Very early relapsed FL may warrant consideration of allogeneic over autologous transplantation in the appropriate setting.